Dependent Personality in Depressed Older Adults: A Case Report and Systematic Review. (September 2021) - Heintz, Hannah L.; Freedberg, Alexis L.; Harper, David G.
Personality pathology in older adults is largely understudied. Here, we present a case report of an older adult who presented to an inpatient geriatric psychiatry unit with dependent personality traits in the context of chronic major depressive disorder, followed by a systematic review of the literature to identify research regarding the diagnosis and prevalence of dependent personality in depressed older adults. We identified 11 studies relevant to this topic. Synthesis of these data revealed that dependent personality is generally more common in depressed older adults compared to other personality disorders. However, studies were limited by small sample sizes and the use of assessments not validated for use in older adults. Therefore, it is difficult to draw conclusions from the available data. Potential implications for patient outcomes and health care services utilization are discussed. Our review highlights the need for larger scale research and personality assessments which are sensitive to age-related factors in order to draw evidence-based conclusions.